Performance of concrete block pavement on sloped road section - Mudiyono, Rachmat; Md. Nor, Hasanan; Hainin, Mohd. Rosli; Ling, Tung Chai (2007)
The construction of Concrete Block Pavement (CBP) on slopes provides interesting challenges for road engineers. The horizontal (inclined) forces exerted on the road surface are greatly increased due to traffic accelerating (uphill) and braking (downhill). These forces will cause horizontal creep of the blocks down the slope, resulting in opening of joints at the top of the road section. The objective of this study was investigate the effect of parameters include degree of slope, laying pattern, joint width, and thickness of paving block on the performance of CBP on slopes. A laboratory-scale test was used to study these parameters based on steel frame horizontal force and push in tests. Three different laying pattern (stretcher bond, herringbone 90o and herringbone 45o) and joint width (3 mm, 5 mm and 7 mm) were used in the test program. The pavement responses are characterized in terms of horizontal creep and deflection due to applied load for half of an allowable single axle limit. The results indicate that herringbone 45o laying pattern and 3 mm joint width performed best on slopes section. The 100 mm paver thickness is found to be more stable than 60 mm thickness from aspect horizontal force resistant. The results also indicate that the increase of the slope increase the horizontal creep, but decrease of the pavement displacement.